Exploring the Evolution of Electric Vehicle Charging Infrastructure: A Bibliometric Perspective on Public Electric Vehicle Charging Station Location Planning - Notopramono, Hanna; Irawan, Mohammad Isa (Institut Riset dan Publikasi Indonesia, 2026)
The rapid expansion of electric vehicles (EVs) is a crucial factor in achieving low-carbon mobility and promoting sustainable regional development. The attainment of this objective depends on technological advancement, institutional readiness, spatial equity, and governance capabilities. The establishment of Stasiun Pengisian Kendaraan Listrik Umum (SPKLU) in Indonesia must be understood within a framework that connects infrastructure planning to social, economic, and political factors. This research analyzes the evolution of international scientific dialogue regarding EV charging infrastructure through a bibliometric lens, focusing on publications from 2010 to 2025. This study utilizes Scopus data and analytical tools, including VOSviewer and Publish or Perish, to identify leading authors, key journals, and emerging subject trends. The results suggest that future SPKLU planning in Indonesia requires an integrated framework that aligns technological precision with public governance principles. This approach should account for decentralization dynamics, regional disparities, and institutional capacity, ensuring that improvements to EV infrastructure contribute to carbon-reduction goals while fostering equitable and sustainable regional development.